Sodāmības institūta ģenēze un attīstība - Zuļķis, Jānis (Latvijas Universitāte, 2015)
Autoraprāt pagaidu risinājums, lai kaut daļēji tiktu ievērots samērīgums un sasniegts mērķis, būtu nepieciešams lielāku uzmanību pievērst normatīvajos aktos noteiktajiem aizliegumiem, tos sakārtojot un ieviešot samērīgus termiņus. Lai gan šāda pieeja vienalga neizvērtēs katru konkrēto gadījumu un aizliegums būs vairāk universāls nekā individuāls, tomēr tas var tikt pielāgots atbilstoši tiesiskajai realitātei un kļūt samērīgāks. Piemēram, aizliegumu nosakot uz desmit gadiem, nevis uz mūžu.

Bachelor thesis covers actual and practically most significant problems related with criminal records. Work analyzes compliance of institute of criminal record with criminal records and punishment legal goals. All problems analyzed in context of reform in Criminal law of December 2012 as its article 35 contains new punishment goals, which are aimed at re-socialization and the restoration of justice. Although the criminal records are not the classic type of punishment, in fact, it acts like one of the restriction instruments of persons rights. Persons re-socialization is not and must not be a goal in itself, however, thesis analyze results of criminal records as contradiction with existing regulation in Criminal law. At thesis as a defensible thesis raised a proposal for exclusion of Criminal record institute from the Criminal law.
Genesis and development of criminal records
Keywords: Juridiskā zinātne; sodāmība; personas tiesību ierobežošana; sods; soda mērķi; juridiskas sekas